Ihab Hassan criticism of the Arab Spring revolutions - Mohammed, Raniah Salam; Awada, Hanan Ali (Al-Adab Journal, 2022)
Our research includes the political views of Ihab Habib Hassan (1925-2015), in particular his criticism of the “Arab Spring.” We mentioned four revolutions, for example: Tunisia, Egypt, Libya, and Yemen. At the outset, we explained with a simplified presentation the period during which the heads of those countries ruled, and the reasons that accelerated the emergence of those revolutions. Among these reasons: political corruption, dictatorship, poverty, unemployment .... We have explained his opinion on those revolutions, which led to the overthrow of all the presidents of these countries. We found that Hassan, on the one hand, supports it, and opposes some side interventions, on the other. He placed the blame on dictatorial political rulers, and rejected the method of suicide bombers to blow themselves up.